Coproporphyrinogenase in a Respiration-deficient Mutant of Yeast Lacking All Cytochromes and Accumulating Coproporphyrin - Miyake, Setsuko (1968)
In an earlier report, a respiration-deficient mutant of yeast which lacks all cytochromes and hemoproteins and accumulates coproporphyrin was described. This respiration-deficient mutant was temperature-sensitive and resulted from the single chromosomal gene(cyt). In this study, the activity of coproporphyrinogenase, catalyzing the conversion of coproporphyrinogen to protoporphyrinogen, was assayed in the cyt mutant and wild strains. Coproporphyrinogenase activity was 10 times higher in the cyt mutant than in the wild strains. Cells of the cyt mutant grown at 20 C had less activity than those grown at 35 C. The Michaelis constants, pH optima, and temperature activations of the enzymes of the cyt mutant and the wild strains were similar. The significance of the higher activity of this enzyme in the cyt mutant, in which this enzymatic step is apparently blocked in vivo, is discussed.